The location of high order services in Istanbul - Lale Berkoz (European Regional Science Association (ERSA), 1998)
The interurban location of high-order service activities was investigated by researchers during the 1980s. But a few studies have concentrated on the intra-metropolitan location of high-order service activities. Most studies have recently focuced on the decline of the central business district (CBD) and rise of suburban areas. These studies have shown that the CBD may be losing its economic and locational importance as a result of the impact of advanced communication technology. The objective of the research summarized in this paper is to evaluate the intra-metropolitan locational behavior of high-order services (finance, insurance, real estate, investment and holding companies) in the Istanbul metropolitan area. The method of factor analysis is utilized to define factors which are important in determining office location patterns. Key words: High-order service, decentralisation, location
Keywords: 330